International Association for the Study of Pain Presidential Task Force on Cannabis and Cannabinoid Analgesia: research agenda on the use of cannabinoids, cannabis, and cannabis-based medicines for pain management. (July 2021) - Haroutounian, Simon; Arendt-Nielsen, Lars; Belton, Joletta; Blyth, Fiona M.; Degenhardt, Louisa; Di Forti, Marta; Eccleston, Christopher; Finn, David P.; Finnerup, Nanna B.; Fisher, Emma; Fogarty, Alexandra E.; Gilron, Ian; et al.
Abstract : Abstract: The President of the International Association for the Study of Pain established a task force on cannabis and cannabinoid analgesia to systematically examine the evidence on (1) analgesic pharmacology of cannabinoids and preclinical evidence on their efficacy in animal models of injury-related or pathological persistent pain; (2) the clinical efficacy of cannabis, cannabinoids, and cannabis-based medicines for pain; (3) harms related to long-term use of cannabinoids; as well as (4) societal issues and policy implications related to the use of these compounds for pain management. Here, we summarize key knowledge gaps identified in the task force outputs and propose a research agenda for generating high-quality evidence on the topic. The systematic assessment of preclinical and clinical literature identified gaps in rigor of study design and reporting across the translational spectrum. We provide recommendations to improve the quality, rigor, transparency, and reproducibility of preclinical and clinical research on cannabis and cannabinoids for pain, as well as for the conduct of systematic reviews on the topic. Gaps related to comprehensive understanding of the endocannabinoid system and cannabinoid pharmacology, including pharmacokinetics and drug formulation aspects, are discussed. We outline key areas where high-quality clinical trials with cannabinoids are needed. Remaining important questions about long-term and short-term safety of cannabis and cannabinoids are emphasized. Finally, regulatory, societal, and policy challenges associated with medicinal and nonmedicinal use of cannabis are highlighted, with recommendations for improving patient safety and reducing societal harms in the context of pain management. Abstract : Supplemental Digital Content is Available in the Text. Preclinical and clinical knowledge gaps on efficacy and harms of cannabis, cannabinoids, and cannabinoid-based medicines informed a research agenda to address these gaps across the translational pain research spectrum.